Dental conferences: Are they good for education? - Gupta, Dr. Suruchi; Thosar, Dr. Nilima; Baliga, Dr. Sudhindra; Rathi, Dr. Nilesh; Fulzele, Dr. Punit (IJRDO- Journal of Educational Research, 2017)
The current status of dental education in India has some pivotal challenges. There is a vital needto concentrate beyond the humdrum classroom learning and curriculum which can be partlyaddressed by sharing ideas with experts and community. There is a need to refine and reconstructthe current education pattern to create pioneers in the field of dentistry for meeting the expandingdemands. Dental students in India are trained to excel theoretically, but there seems to be avacuum between the theoretical and its clinical implications. Dental conferences endow with avariety of approaches and strategies related to management and quality improvement of dentalclinic as well as explore new ideas and concepts. The aim of this article is to discuss the benefitsassociated with attending conferences as well as highlighting the scope for improvement ofconduction of such conferences.